1992
DOI: 10.1128/iai.60.5.1908-1912.1992
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin treatment accelerates middle ear inflammation in experimental pneumococcal otitis media

Abstract: Most Streptococcus pneumoniae strains are killed by very low concentrations of penicillin and other 13-lactam antibiotics, yet middle ear inflammation and effusion persist for days to weeks after treatment in most cases of pneumococcal otitis media. To study the effect of 13-lactam antibiotic treatment on pneumococci and the middle ear inflammatory response during pneumococcal otitis media, we measured concentrations of pneumococci, inflammatory cells, and lysozyme in middle ear fluid (MEF) by using the chinch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Tuomanen et al (24) showed that ampicillin treatment of rabbits with pneumococcal meningitis led to a transient but significant increase in meningeal inflammation. We recently made a similar observation by using the chinchilla otitis media model (11). If, indeed, pneumococcal cell wall fragments induce and sustain middle ear inflammation, understanding the mechanisms by which these components are cleared from the middle ear becomes important and may have implications for future antipneumococcal treatments.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Tuomanen et al (24) showed that ampicillin treatment of rabbits with pneumococcal meningitis led to a transient but significant increase in meningeal inflammation. We recently made a similar observation by using the chinchilla otitis media model (11). If, indeed, pneumococcal cell wall fragments induce and sustain middle ear inflammation, understanding the mechanisms by which these components are cleared from the middle ear becomes important and may have implications for future antipneumococcal treatments.…”
Section: Discussionmentioning
confidence: 74%
“…The cell wall digests were in solution. Native-cell wall inoculum sizes were 10.0, 1.0, and 0.1 ,ug, and the cell wall digest inoculum size was 10.0 ,ug; the 10-,ug inoculum is approximately 108 cell equivalents, which equals the concentration of pneumococci in chinchilla middle ear effusion 24 to 48 h after 40 CFU are injected into the ear (11).…”
Section: Methodsmentioning
confidence: 99%
“…Beta-lactam antibiotic treatment accelerated type 3 S. pneumoniae-induced inflammation in the rabbit meningitis model (36) presumably because treatment lysed pneumococci, releasing cell envelope fragments such as cell wall or cytoplasm products such as pneumolysin into the surrounding environment. We observed a similar acceleration of inflammation in the chinchilla otitis media (OM) model using type 3 and 7F S. pneumoniae (19,34). Timing of penicillin treatment with regard to bacterial concentration in MEF was a critical determinant of the middle ear (ME) inflammatory response (34).…”
mentioning
confidence: 66%
“…Streptococcus pneumoniae is the most prevalent middle ear bacterial pathogen, cultured from approximately 40% of middle ear fluid (MEF) samples from children with acute otitis media (AOM) (2,9) and 7% of MEF samples from children with chronic otitis media with effusion (OME) (2). We have studied the pathophysiology of pneumococcal AOM using the chinchilla otitis media model (18,19,23,28,29) and in the guinea pig model otitis media model induced by Haemophilus influenzae (17,24,25) and Moraxella catarrhalis (27). Inflammatory cells, lysozyme, and oxidative metabolic products have been recognized as being important contributors to acute middle ear inflammation.…”
mentioning
confidence: 99%